Individual and Simultaneous Photodegradation of Trimethoprim and Sulfamethoxazole Assessed with the Microbial Assay for Risk Assessment - Grzegorz Nałęcz-Jawecki; Milena Wawryniuk; Weronika Kopczyńska; Joanna Giebułtowicz (Molecules)
Co-trimoxazole is an antibacterial drug, a mixture of sulfamethoxazole (SMX) and trimethoprim (TMP) in a ratio of 5:1. Due to the different susceptibility of both components to decomposition under the influence of sunlight, the aim of the study was to assess the change in bacteriostatic activity during irradiation of the mixture of these antibiotics in a sunlight simulator. The bacteriostatic activity was assessed using a Microbial Assay for Risk Assessment (MARA), monitoring drug concentrations as well as the formation of photodegradation products using liquid chromatography (LC). The toxicity analysis of the SMX and TMP mixture showed synergistic bacteriostatic activity for six bacterial strains. This activity was maintained even during sample irradiation when 80–90% of SMX was degraded. This may indicate the bacteriostatic effect of SMX photoproducts and/or the lack of necessity to maintain a 5:1 ratio between SMX and TMP to maintain a strong effect of the mixture of these antibiotics. Analysis using LC with a high-resolution mass spectrometry detector revealed the presence of 11 SMX degradation products, including two with preserved sulfonamide structure, which may exhibit bacteriostatic activity.